PENGARUH PENGGUNAAN METODE DISKUSI TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN SISWA KELAS III SEKOLAH DASAR - Maimunah, Lia Dionisia; Halidjah, Siti; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe problem in this study is "How does the influence of the use of the discussion method on the learning outcomes of citizenship education in third grade students of 09 Pontianak Barat Elementary School?". This study aims to determine the effect of the use of discussion methods on the learning outcomes of Citizenship Education Class III students. The population in this study were all students of class III A, amounting to 30 students, III B totaling 30 students, III C totaling 30 students and III D totaling 34 students. The research sample consisted of III A 30 students in the control class and III C 30 students in the experimental class. Based on statistical calculations the average post-test learning outcomes of the control class is 66.10 and the average post-test of the experimental class is 70.70. From this explanation, it can be concluded that there is an influence of the use of the discussion method on the learning outcomes of Citizenship Education class III students of 09 Pontianak Elementary School in West Pontianak in the medium category.Keyword : Citizenship Education, Discussion Methods, Influence, Learning Outcomes.